Pelatihan Akuntansi bagi Usaha Mikro, Kecil, dan Menengah (UMKM) Penjualan Ban : Accounting Training for Micro, Small, and Medium Enterprises (MSMEs) Tire Sales - Irawan , Candra (Assoeltan: Indonesian Journal of Community Research and Engagement, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the tire sales sector play an important role in the local economy; however, many of them still experience fundamental problems in financial management, particularly in bookkeeping and the preparation of financial statements. Weak accounting practices limit the ability of MSME owners to understand their actual financial condition and to make rational business decisions. This community service activity aimed to strengthen the accounting capacity of a tire sales MSME through participatory accounting training and mentoring. The service employed a Participatory Rural Appraisal (PRA) approach, which positioned the MSME owner as an active subject in identifying problems, mapping daily transactions, and formulating practical bookkeeping solutions. Data were collected through participatory interviews, direct observation, documentation of transaction records, and reflective discussions. The results indicate a significant improvement in the partner’s understanding and practice of simple bookkeeping, reflected in the ability to systematically record daily transactions and to prepare a basic income statement and balance sheet. The PRA-based approach proved effective in transforming accounting knowledge into sustainable managerial practice because it was grounded in the real context of the business. In conclusion, this community service demonstrates that participatory accounting mentoring can effectively address financial management problems in MSMEs. Scientifically, this program contributes to the development of participatory-based community service models that bridge the gap between normative accounting concepts and practical MSME needs.